The effects of Saccharomyces cerevisiae strains carrying alcoholic fermentation on the fermentative and varietal aroma profiles of young and aged Tempranillo wines - Denat, Marie (2021)
Ten different Saccharomyces cerevisiae strains fermented semi-synthetic musts containing a Polyphenolic and Aroma Precursor Fraction (PAF) extracted from Tempranillo grapes. Aroma compounds were studied by Gas Chromatography (GC), GC-Olfactometry and GC-Mass Spectrometry (MS), during fermentation by trapping volatilized aroma, immediately after fermentation and after accelerated aging. Volatiles lost by evaporation during fermentation are mostly fermentative compounds and not grape-related odorants. Isobutanal and some esters are mostly lost during fermentation. In many cases the impact of yeast strain is evident only after aging. Strains could be classified into 3 major clusters with marked differences in fermentative and varietal profiles. Linalool and geraniol were found to have fermentative origin. S. cerevisiae yeast strains can effectively modulate varietal aroma, likely through specific enzymatic activities acting on grape phenolic acids and norisoprenoid aroma precursors and may be specifically used to mitigate some aging-related off odours, such as massoia lactone, guaiacol or TDN.